A Discourse Analysis of Zuckerberg’s Pragmatic Identities’ Construction based on Adaptation Theory - Li, Yuxin (Advances in Social Sciences Research Journal, 2021)
People construct different pragmatic identities in everyday talk and the process of building identities usually adapts to the context. To be specific, entrepreneurs represents himself and the company when uttering to the outside society and the construction of entrepreneur’s identity is related to the company’s image. They are inclined to use intertextuality resources to build connection with the potential audience. Therefore, in this research, the author analyzed an entrepreneur’s speech discourse to describe what pragmatic identities are constructed and how does the construction adapt to the speaking context. To answer these questions, the author conducted a discourse analysis to illustrate relationship between the language use and physical, social and mental world based on Adaptation Theory. The results presented that the entrepreneur builds various master identities, interpersonal identities, and personal identities with intertextuality language resources to adjust to the speaking context. This study suggested that entrepreneurs are supposed to improve the skill of manipulating their discourse strategies to build close connection with potential listener.